Dietary Supplementation With Various Fat Oils Affect Phytohemagglutinin Skin Test in Broiler Chickens - Al-Khalaifah, Hanan; Al-Nasser, Afaf (Frontiers in Immunology, 2020)
This study aimed to investigate the effect of different supplemental oils on the immune status of broilers. One-day-old Cobb 500 chicks were randomly distributed into eight batteries and fed eight experimental diets. There were 680 broilers, 85 birds per battery. The experimental oils were all used at 10% of the total diet. Each dietary treatment (TRT) contained one of the following oils: TRT 1=control group that received a basal diet+ soybean oil (SO); TRT 2=basal diet as in TRT 1 + sunflower oil (SFO); TRT 3= basal diet as in TRT 1+canola oil (CO); TRT 4=basal diet as in TRT 1+flaxseed oil (FLO); TRT 5=basal diet as in TRT 1+fish oil (FO); TRT 6=basal diet as in TRT 1+mix of fish oil and soya oil (SO+FO); TRT 7=basal diet as in TRT 1+algal biomass oil (DHA); TRT 8=basal diet as in TRT 1+echium oil (EO). Samples were taken from 10 birds per treatment (n=10). The parameters investigated involved measurement of immune organ weights as a general indicator, haemocytometric measurements, intestinal microbial count and hindgut acidosis, hindgut volatile fatty acids, and cellular immune response using PHA-test. The use of the different treatments did not affect the general health status of the chickens and the mortality was minimal with no signs of illness . At 3-wk of age, there was no significant effect observed in the microbial counts of the intestine. However, at 5-wk of age, the highest microbial count was significantly observed for broilers fed EO (7.30%), closely followed by SFO (6.95%) and the least microbial counts were observed for CO (5.63%). No significance was observed for LAB and Salmonella. There was no significance observed for the effect of the dietary treatments on the hindgut volatile acid in the broilers. Wattle swelling changes were significant between dietary treatments. The results revealed that dietary FLO, FO, and DHA oils induced higher cellular response than the other treatments (P=0.035), representing higher cellular response in these groups. In conclusion, supplemental oils rich in n-3 PUFA may enhance the immune response in broiler chickens, represented by the intestinal microbial counts and the cellular immune response.